Crowds Ethnographic Encounters (Edition 1) - Steffen, Megan (Routledge, 2020)
What exactly is a crowd? How do crowds differ from other large gatherings of people? And how do they transform emotions, politics, or faith? In Crowds, contributors draw on their experiences and expertise to reflect on their encounters with crowds. Each chapter examines a particular crowd or conception of crowdedness to provide an analysis of how, when, where-and with whom-crowds form in different contexts, as well as their purpose and the practical effect the experience has on both the participants and their environment. The wide selection of case studies ranges from the crowds that form every year during the Hajj, to New Year celebrations in China, commuters on the Delhi metro, public prayer in Nigeria, online mobs in Bangladesh, and the crowds that have emerged during protest movements in Thailand and Syria. Crowds makes a key contribution to establishing an anthropological theory of crowds and will be an essential read for both students and researchers.